Not worth watching? Examining gender bias, perceptions of ability, and consumer behaviour for the Women’s Australian Football League - Mackenzie R. Glazbrook; Sarven S. McLinton; Stephanie N. Webb; Mikaela S. Owen (Australian Journal of Psychology)
Objective Despite the increasing presence of women in professional sport, gender biases continue to shape consumer perceptions and engagement. This study examines how gendered attitudes influence evaluations of athlete quality and, in turn, consumer intentions towards the AFLW.Method A community sample (N = 862) completed an online survey assessing gender attitudes, and beliefs about sport and masculinity, and perceptions of athlete quality in football.Results Multigroup path analysis revealed differences in consumer perceptions of women’s and men’s football. Traditional attitudes towards gender and masculinity were significantly related to negative perceptions of women footballers’ abilities, which were also associated with reduced desire to watch and attend AFLW matches.Conclusions These results highlight the role of gender biases in shaping public engagement with women’s sport. Addressing these biases, particularly in media representation and marketing, may be key to increasing consumer investment in women’s football and promoting greater gender equity in sport.